Keanekaragaman dan kelimpahan kumbang daun (Coleoptera: Chrysomelidae) pada empat tipe penggunaan lahan yang berbeda di Taman Nasional Bukit Duabelas dan Hutan Harapan, Provinsi Jambi - Rosyid Amrulloh; Woro Anggraitoningsih Noerdjito; Bonjok Istiaji; Purnama Hidayat; Damayanti Buchori (Jurnal Entomologi Indonesia, 2022)
Deforestation has a negative impact toward ecosystem and diversity. Landuse change has been known to negatively impact insect like ant and beetle in Jambi Province. This research aims to study the diversity, abundance, and composition of the leaf beetle in the Bukit Duabelas National Park (TNBD) and Harapan Forest landscape. Insect sampling was carried out using canopy fogging method. Four core plots were determined in each land use (as replicates) and each plot consist of three as subplot. Insect was collected in 16 traps (size 1 m x 1 m) that was installed under plant canopy prior to fogging process. The collected sample was sorted and identified in the Biocontrol Laboratory, Plant Protection Department, Faculty of Agriculture, IPB University. Total of 1,040 individuals leaf beetles were collected, belonging to 6 subfamilies and 127 morphospecies. The result of this research showed that a different lanscape has no effect give impact to insect abundance. Different landuse however does significantly impact the abundance and diversity of leaf beetle (Coleoptera: Chrysomelidae).